EXPLORING THE IMPACT OF RISK FACTORS, PREVENTIVE MEASURES, AND MANAGEMENT STRATEGIES ON SURGICAL SITE INFECTIONS IN GENERAL SURGERY: A COMPREHENSIVE ASSESSMENT - Hamid ur Rehman,; Atif Iqbal,; Ibrar Ahmad,; Hina Fayyaz,; Liaqat Ali,; Javed Iqbal,; Qazi Mohammad Hameed, (Journal of Ayub Medical College Abbottabad, 2024)
Background: Surgical site infections (SSIs) pose significant challenges in healthcare, leading to prolonged hospital stays, increased morbidity, and economic burden. Understanding the interplay between risk factors, preventive measures, and management strategies is crucial for effective infection control in general surgery. This study aimed to comprehensively assess the impact of various risk factors, preventive measures, and management strategies on surgical site infections in the context of general surgery. Methods: The study was conducted atJinnah International Hospital Abbottabad, involving a study population of 120 patients undergoing general surgical procedures from May 2023 to April 2024. A retrospective analysis of patient records was performed to identify risk factors associated with SSIs. Additionally, preventive measures implemented preoperatively, intraoperatively, and postoperatively were evaluated. Management strategies employed for treating SSIs were also reviewed. Results: The analysis revealed several significant risk factors contributing to the development of SSIs, including comorbidities, prolonged surgical duration, and inadequate preoperative preparation. Preoperative measures such as appropriate patient screening and optimization, intraoperative techniques like strict aseptic protocols, and postoperative interventions such as timely wound care significantly influenced SSI rates. Furthermore, effective management strategies such as early detection, antimicrobial therapy, and surgical debridement played pivotal roles in controlling SSIs and reducing associated complications. Conclusion: Our findings underscore the importance of a multifaceted approach involving identification of risk factors, implementation of preventive measures, and prompt management strategies to mitigate the incidence and impact of surgical site infections in general surgery. Comprehensive infection control protocols tailored to individual patient needs are essential for optimizing surgical outcomes and enhancing patient safety.